How much consciousness is there in complexity? - Koculak, Marcin; Wierzchoń, Michał (Frontiers in Psychology, 2022)
The notion of complexity receives currently significant amount of attention in neuroscience, mostly through the popularity of the Integrated Information Theory (IIT). It has proven successful in research centred on discriminating states of consciousness, while little theoretical and experimental effort was directed towards studying the content. In this paper, we argue that exploring the relation between complexity and conscious content is necessary to properly understand the importance of information-theoretic measures with consciousness. We outline how content can be experimentally operationalized and how rudimental testable hypotheses can be formulated without the necessity for inclusion of formalisms of IIT. This approach would not only allow for better understanding of aspects of consciousness captured by complexity, but could also facilitate comparisons of theories of consciousness.